THU0415 EXPLORATORY PROTEIN PROFILING OF HUMAN SYNOVIAL FLUID FROM KNEE OSTEOARTHRITIS. (June 2019) - Ali, Neserin; Tjörnstrand, Jon; Neuman, Paul; Folkesson, Elin; Hughes, Velocity; Önnerfjord, Patrik; Englund, Martin
Abstract : Background: There is a lack of valid and robust biomarkers in the field of OA diagnosis, prognosis, and treatment evaluation [1]. Synovial fluid is in direct contact with articular cartilage, ligament, meniscus and joint capsule it is therefore an excellent sample to explore the protein profile in which could provide pathogenesis information from several surrounding parts. Objectives: The aim with this project was to perform mass spectrometry (MS) of human synovial fluid using a global discovery approach, to identify biomarker candidates associated with meniscus degradation and/or knee OA. Methods: Synovial fluid was sampled from 3 different subject groups: i) end-stage medial compartment knee OA patients undergoing arthroplasty (n=11, age range 55-80 years), ii) knee arthroscopy patients who typically had a degenerative meniscal tear (n=7, age range 50-64 years), and iii) deceased human donors without known chronic knee disease (n=13, age range 19-79 years). All synovial fluids were centrifuged and freshly frozen and stored at -80°C. For the analysis, 50 µL of synovial fluid was mixed with MS-safe proteinase inhibitor cocktail, hyaluronidase, depleted, reduced, alkylated, precipitated, digested with sequencing grade trypsin (Promega), filtered and desalted. The samples were further analyzed with an EASY-nLC 1000 coupled to an Orbitrap Fusion mass spectrometer using data-independent acquisition. The raw MS data were further analysed with Spectronaut™ for protein identification and quant data extraction. Differences in protein levels were analyzed in two steps: 1) Donors vs arthroplasty 2) Between all 3 different groups. Analyses were adjusted for age, gender and weight. Differentially expressed proteins between the groups were clustered using Pearson correlation coefficient as the distance metric. Results: In total, 529 proteins were identified in the 31 different synovial fluid samples analyzed. Principal component analysis suggested a profound difference between the protein profiles of synovial fluid from donors vs arthroplasty patients, while the arthroscopy group had a protein profile that was in-between donors and the arthroplasty group (Figure 1A ). Statistical differential analysis yielded significant differences in the levels of 43 proteins comparing donors vs arthroplasty patients. 36 proteins differed between the 3 groups when comparing all groups in the same statistical model. Extracellular matrix proteins like collagens and aggrecan showed higher expression in donors than in arthroplasty patients. Collagen on the other hand was higher in arthroscopy patients compared to donors. Decorin was significantly higher in donors compared to both arthroscopy and arthroplasty patients. The differentially expressed proteins associated with the inflammatory response were higher in the arthroscopy group compared to both donors and arthroplasty patients. Generally, extracellular matrix proteins like collagen1/2 were positively correlated with lipoproteins like APOB and APOA but negatively correlated with acute phase proteins like PON1(Figure 1B ). Conclusion: There is a profound difference in the protein profile of synovial fluid in donors vs knee OA patients (Figure 1 ). The inflammatory response seems to be higher in the early stages of OA than in later stage. Our findings emphasize the importance of OA staging in the development and use of biomarkers. Reference: [1] Mobasheri A. Osteoarthritis year 2012 in review: biomarkers. Osteoarthritis and Cartilage. 2012 Dec 1;20(12):1451-64. Acknowledgement: We would like to acknowledge the Foundation for Research in Rheumatology (FOREUM) for funding. Disclosure of Interests: None declared